Dynamic work trajectories and their interplay with family over the life course - Han, Xiaowen; Mortimer, Jeylan T. (Frontiers in Sociology, 2023)
This review examines major bodies of literature, interrelated but usually considered separately, focused on work trajectories and their intersections with family dynamics through the life course. It begins with a consideration of the life course paradigm, which draws attention to the temporal dimensions of human lives, and recently developed analytic techniques that are well-suited to empirical investigation of life course transitions and trajectories over time. The review proceeds to examine empirical research on work career mobility (including both inter- and intra-generational mobility) measured as either trajectories of continuous outcomes or sequences of categorical outcomes, and their long-term consequences for socioeconomic attainment. Work-family trajectories are then addressed, focusing on the impacts of family on work, notably expressed in the motherhood wage penalty, and how family structure and processes affect long-term labor market outcomes. Research documents considerable heterogeneity in work-family dynamics over the life course across social groups with unequal resources. The review concludes with an assessment of the interplay of work and family trajectories studied longitudinally and makes recommendations for future research. It is argued that while extant studies of the work-family interface are compatible with, and sometimes deliberately reflect, a life course perspective, these bodies of research would benefit from more fully incorporating the life course principles of “agency” and “time and place”.